Festival as Cultural Branding and Regional Identity: Study of Sagarurung festival at Penukal Abab Lematang Ilir Regency - Muh Yahyaddin; Nadia Chairunnisa Andra Shita Marini; Esxi Martia Gusma; Meisya Anggraini (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study aims to analyze how the Sagarurung Festival as a cultural branding strategy for strengthening regional identity and cultural promotion in Penukal Abab Lematang Ilir (PALI) Regency, Indonesia. A mixed methods approach with qualitative dominance was employed by integrating qualitative data from in-depth interviews, participant observation, and document analysis with quantitative assessment through SWOT analysis using IFAS and EFAS frameworks. Data were collected from government representatives, festival organizers, cultural practitioners, MSME actors, and local communities, then analyzed through thematic analysis and strategic evaluation. The findings reveal that the Sagarurung Festival functions as a platform for transforming local cultural resources into symbolic representations of PALI Regency through cultural performances, smoked Sagarurung fish as culinary heritage, and community participation. The IFAS and EFAS results position the festival in quadrant I (Aggressive Strategy), indicating strong cultural assets and favorable external opportunities. However, challenges remain in cultural curation, digital promotion, documentation, and structured storytelling. This study contributes to cultural branding and festival studies by demonstrating how sub-national festivals can support regional identity construction and sustainable cultural promotion through the integration of cultural resources and strategic development.